A influência da mudança na cultura e no clima organizacional: o caso do Instituto Federal Da Paraíba (IFPB), Campus Sousa - Carneiro, Joselma Mendes de Sousa (2017)
The present work deals with the change implemented by Law 11,892 / 2008, which transformed the Brazilian educational system in what refers to middle level schools, known up to that time as Techniques, Agrotechniques and Federal Centers of Education (CEFETs), since it promoted the Integration of these schools throughout Brazil. In a special way, the Agrotechnical Schools, in a total of 39 (thirty-nine) units, lost the autonomy they had because they were local and adhered to the new management model. In the state of Paraíba, the Federal Agro-technical School of Sousa, which after the change became the Federal Institute of Paraíba (IFPB), Campus Sousa was the object of this research whose general objective was to analyze the influence of the change on the culture and the organizational climate of the IFPB , Campus Sousa and the specific objectives were: Describe the organizational culture of the IFPB, Campus Sousa, during the period of change from Federal Agrotechnic School to Federal Institute, with Law 11,892 / 2008, in the period of 2008 - 2015; Identify the impact of the change caused by Law 11892/2008 on organizational processes; Describe the current situation of the organizational climate of Campus Sousa from the perspective of the servers; Understand how organizational change, culture and climate influenced the identity of the IFPB. To reach the objectives, the case study was used as methodology. Regarding nature, the research was exploratory and descriptive, making use of the qualitative strategy and made use of two instruments to collect data: the interview and the questionnaire. In the analysis of interview data, the content analysis technique was used, following the definition, characteristics and stages of Franco (2015) and Bardin (2016); Already the analysis of the questionnaires was given by simple frequencies, percentages and representation in graphs. At the end of the research, it is verified that the proposed objectives were reached, and it can be inferred that the change influenced the organizational culture and the organizational climate, modifying beliefs, rituals and values and that, despite being at an advanced stage, the organization Does not have a definite real identity, necessitating a more effective process of socialization of formal identity for this to occur.